Sistem Informasi Manajemen Pencatat Kelahiran Bayi - Erviani, Diah; Hudallah, Noor; Suryanto, Agus (Jurusan Teknik Elektro Universitas Negeri Semarang, 2017)
The purpose of this research is to produce software of Management Information Systems Registry of Births Baby Web-based using PHP and MySQL in the office of the village hall Penundan subdistrict Batang district Banyuputih viable, practical and easy to use. The expected benefits of this research is to provide practicality and ease the process of recording births and birth data archiving. The research method used is a Research and Development (R & D). Functional testing system using blackbox testing performed by 10 students, due diligence review conducted by 2 lecturers expert system based on McCall quality models and test the practicality of implementation and ease of use of the system is done by 5 village officials. Data collection techniques by observation, interviews and questionnaires. Data analysis techniques in the study using a descriptive system with the percentage of research instruments in the form of a checklist or a selection of data called Likert scale. Conclusions from this research is the Management Information System Registry of Births Baby has successfully created the method of Research and Development, the results of feasibility test on the criteria of